Improved Torque Ripple of Switched Reluctance Motors using Sliding Mode Control for Electric Vehicles - Vinh, Vo Quang; Ha, Vo Thanh (Engineering, Technology & Applied Science Research, 2023)
This study describes the direct torque control-DTC approach, based on the Sliding Mode Control (SMC) technology with chattering reduction, for reducing the torque ripple of the Switched Reluctance Motor (SRM). The SRM torque control loop has been given the SMC treatment to account for the low-frequency fluctuations in the torque output. To maintain a consistent motor speed, the sliding mode controller modifies the value of the reference current. The findings demonstrate that the constant sliding mode controller is superior to PI controllers at lowering the motor's torque ripple, compensating for its nonlinear torque characteristics, and rendering the drive insensitive to parameter changes. MATLAB/SIMULINK simulation has been used to show how well this SMC performs. The performance of the proposed SMC method has been demonstrated by simulation in MATLAB/SIMULINK with a three-phase 8/6 pole, and a 2kW SRM.